Ice build-up rate on custom-designed external melt thermal energy storage (TES) evaporator - mathematical modeling and validation - Bongat, Ruben A. (2012)
External melt thermal energy storage (TES) system is a load-side management technique that shifts the operation of air-conditioning compressors from on-peak to off-peak hours. This is attained by producing ice during night time and using it to cool a space the following day, when electricity cost is high. The option to explore TES in central air-conditioning system is a response to the need for air-conditioning equipment, with lower operating cost than the conventional water chiller. The usual stumbling blocks in the widespread use of TES equipment for air-conditioning are: (i) large equipment footprint which affects the income generated thru rentable spaces in commercial installations and (ii) high first cost due to more expensive imported equipment which affect the economic viability of the project. In this regard, locally fabricated TES evaporator coil at compressor-aided, partial storage mode with maximum design ice thickness of more than 72mm (2.5 in.) was used. Simulation analysis shows that custom-designed., locally fabricated TES cooling coil, with instantaneous cooling demand of about 1,147 kW (326.2 TR) and ice thickness of 2.85-in. will require an increase in initial investment by about 14.26% compared to conventional water chiller of the same capacity. However, its annual projected power consumption will be roughly PhP 911,533 lower, or about 113.54% of water chiller power cost. This will result in 31.88% internal rate of return (IRR) at 5-year cashflow or equal to about 2.55-year simple payback period. Annual TES electricity savings due to COP improvement alone brought by lower ambient conditions is about 2% of the water chiller annual power cost. The initial cost comparison does not include the electrical and piping requirements of the two systems. It is expected that electrical works are cheaper due to smaller compressor as a consequence of compressor-aided scheme. Chilled water pump motors are also smaller due to lower chilled water flowrates as a result of large chilled temperature difference. Also, piping and insulation sizes are smaller due to lower flowrates, which results to cheaper piping, fittings and insulation costs. Considering the combined economic effect of time-of-use (TOU) power rate and improvement in COP, the savings in electricity cost is about 12% of the water chiller annual power cost. This translates to about PhP 911,533 annual electricity cost savings. The mathematical model was developed based on relevant and validated researches, where the freezing equation requires simultaneous solution of: (a) the weight of water converted to ice (b) prevailing TES bulk water temperature (c) all the thermophysical properties of ice expressed as function of bulk ice temperature and (d) correlated compressor capacity based on actual refrigeration system operating parameters. The predicted bulk water temperature was found to have a percentage deviation between 0% and 1.08% based on recorded absolute temperature. The mathematical predictions for pseudo-ice thickness around the cooling coil were found to vary between +14.57% and -17.38% for the entire duration of the data gathering activity, with average deviation in the range of 1.42% and -0.47%.